Modelling distribution and fate of coralligenous habitat in the Northern Adriatic Sea under a severe climate change scenario - Vitelletti, Maria Letizia; Manea, Elisabetta; Bongiorni, Lucia; Ricchi, Antonio; Sangelantoni, Lorenzo; Bonaldo, Davide (Frontiers in Marine Science, 2023)
Due to their well-acknowledged capability in predicting habitat distributions, Habitat Suitability Models (HSMs) are particularly useful for investigating ecological patterns variations under climate change scenarios. The shallow coastal regions of the Northern Adriatic Sea, a sub-basin of the Mediterranean Sea, are studded with coralligenous outcrops recognized as important biodiversity hotspots exposed to the effects of climate change. In this research, we investigate the distributions of the Northern Adriatic Sea coralligenous habitats characterized by diverse species assemblages differently influenced by environmental factors, and provide a projection of how these might be impacted by climate change. Two models (Random Forest and MaxEnt), populated with occurrence data gathered from previous publications, environmental parameters’ from online databases (CMEMS, Bio-Oracle), and a set of dedicated ocean model simulations, are applied in recent past conditions and under a future severe climate change scenario (RCP 8.5). The model performance metrics confirm the ability of both approaches for predicting habitat distribution and their relationship with environmental conditions. The results show that salinity, temperature, and nitrate concentration are generally the most relevant variables in affecting the coralligenous outcrops distribution. The environmental variations projected under climate change conditions are expected to favour the spreading of opportunistic organisms, more tolerant to stressful conditions, at the expense of more vulnerable species. This will result in a shift in the distribution of these habitats, with a consequent potential loss of biodiversity in the Northern Adriatic Sea.